Antibody patenting a practitioner's guide to drafting, prosecution and enforcement - Meier, Jürgen 1957-; Ridderbusch, Oswin (Wolters Kluwer, 2019)
Antibody Patenting' provides a comprehensive and in-depth analysis of all aspects relating to the patenting of antibodies from initial drafting and prosecution to enforcement. Antibodies have revolutionized medicine and biotechnology, and have become indispensable tools in therapy, diagnostics, analytics, and research. Therapeutic antibodies, for example, have come to dominate the ranks of blockbuster drugs, currently accounting for 10 out of the top 15 best-selling medicines. At the same time, a body of case law dealing specifically with the patentability of antibody-related inventions and the enforcement of antibody patents has emerged in major jurisdictions. The, at times, significant divergences between different jurisdictions have been compounded by recent decisions in the United States, most notably Amgen v. Sanofi, 872 F.3d 1367 (Fed. Cir. 2017), which have severely curtailed the possibilities to obtain broad antibody patents. It is therefore essential to understand how antibody inventions are assessed in different jurisdictions in order to secure an optimal patent protection and to successfully enforce such patents.00This book covers 23 of the most important IP jurisdictions worldwide ? i.e., the European Patent Office, France, Germany, Italy, the Netherlands, Poland, Spain, Switzerland, the United Kingdom, Israel, the United States of America, Argentina, the Andean Community (Bolivia, Colombia, Ecuador, and Peru), Brazil, Canada, Chile, Mexico, China, India, Japan, Singapore, South Korea, and Australia